The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/toxins11020121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cellulosic Polymers and Curcumin to Reduce Aflatoxin B1 Toxic Effects on Performance, Biochemical, and Immunological Parameters of Broiler Chickens

Abstract: To evaluate the effect of cellulosic polymers (CEL) and curcumin (CUR) on aflatoxin B1 (AFB1) toxic effects on performance, and the biochemical and immunological parameters in broiler chickens, 150 one-day-old male broiler chicks were randomly allocated into five groups with three replicates of 10 chickens per pen: Negative Control (feed); AFB1 (feed + 2 ppm AFB1); CUR (feed + 2 ppm AFB1 + Curcumin 0.2%); CEL (feed + 2 ppm AFB1 + 0.3% Cellulosic polymers); and, CEL + CUR (feed + 2 ppm AFB1 + 0.3% Cellulose pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“…Although the immune system represents one of AFB1’s targets, few studies have investigated the potential beneficial role of bioactive compounds on the immune organs. For example, curcumin, a powerful plant antioxidant, decreases the weight of spleen and bursa of Fabricius, as well as the ratio of spleen/bursa, in broilers fed AFB1, towards similar values to the control group [ 48 ]. Additionally, in AFB1-intoxicated mice, lycopene, another plant bioactive compound, can alleviate AFB1-induced immunosuppression by increasing spleen weight, spleen coefficient, T-lymphocyte subsets, and IL-2, IFN-γ, and TNF-α gene expression in spleen [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immune system represents one of AFB1’s targets, few studies have investigated the potential beneficial role of bioactive compounds on the immune organs. For example, curcumin, a powerful plant antioxidant, decreases the weight of spleen and bursa of Fabricius, as well as the ratio of spleen/bursa, in broilers fed AFB1, towards similar values to the control group [ 48 ]. Additionally, in AFB1-intoxicated mice, lycopene, another plant bioactive compound, can alleviate AFB1-induced immunosuppression by increasing spleen weight, spleen coefficient, T-lymphocyte subsets, and IL-2, IFN-γ, and TNF-α gene expression in spleen [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some hypotheses concerning the GSM way of action can be formulated based on previous literature studies. The first one, related to the high cellulose content (37.8%) of GSM [ 24 ], has a great potential to adsorb AFB1 by electrostatic attractions and hydrogen bonding, resulting in the formation of a mycotoxin monolayer on its surface [ 48 ]. The second one is based on the ability of polyphenols to form a complex with AFB1 mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Solis-Cruz et al [9] have reported the effects of adding 0.2% curcumin to the diet of broiler chickens (1-21 day old) infected with 2 mg/kg AFB1 in the diet. This study confirmed that adding curcumin to the toxic diet improved the body weight, and decreased the liver weight relative to the whole body weight.…”
Section: Leukocyte Infiltrationmentioning
confidence: 99%
“…Curcumin is a natural polyphenolic compound, with antioxidant, antiinflammatory, and anti-cancer properties. It also offers detoxifying effects and protects against cellular damages caused by radiation and chemotherapy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Banlunara et al (2005) described glucomannan, a polysaccharide from yeast cell walls of Saccharomyces cervisiae, consisting in functional carbohydrates which contains a large surface and number of pores of different sizes to trap a wide range of chemicals as an excellent AFB1 binder [ 29 ]. Also, Solis-Cruz et al (2019) showed that cellulose has a great potential to adsorb AFB1 by electrostatic attractions and hydrogen bonding resulting in formation of a mycotoxin monolayer on its surface [ 30 ]. Waste by-products contain also other bioactive compounds such as polyphenols, polyunsaturated fatty acids (PUFA), etc.…”
Section: Introductionmentioning
confidence: 99%